ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CURAHAN JAM KERJA PEREMPUAN DI KOTA DENPASAR - Anggraeni, Ni Putu Nita; Purwanti, Putu Ayu Pramitha; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.01.TAHUN.2022, 2022)
This study is to analyze the effect of age, education level, type of work, husband's income, and number of family dependents on women's working hours. The population in this study were female residents who worked in Denpasar City and still had a life partner. Determination of the sample using non-probability sampling in the form of quota sampling with 100 respondents. Methods of data collection using observation and interviews. Data analysis used Moderated Regression Analysis. Based on the results of the analysis, it was found that simultaneously age, education level, type of work, husband's income, and number of family dependents had a significant effect on the outpouring of women's working hours in Denpasar City. Partially age, education level, type of work, number of family dependents have a significant and positive effect on women's working hours, but husband's income has a negative and significant effect on women's working hours. The number of family dependents is able to moderate by strengthening the influence of husband's income on women's working hours. Based on the results of the average difference test, women in Denpasar City who work in the informal sector have a higher outpouring of working hours than those who work in the formal sector.